2023
DOI: 10.1159/000529639
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence to Quantitative Assessment of Fundus Tessellated Density in Young Adults with Different Refractions

Abstract: Introduction: To quantitatively assess fundus tessellated density (FTD) and associated factors by artificial intelligence (AI) in young adults. Methods: A total of 1084 undergraduates (age, 17-23 years old) were enrolled in November 2021. The students were divided into three groups according to axial length (AL): Group 1 (AL<24.0 mm, n=155), Group 2 (24 mm≤AL<26 mm, n=578), and Group 3 (AL≥26 mm, n=269). FTD was calculated by extracting the fundus tessellations as the regions of interest (Circle 1, diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…They further examined FTD variations in different refractive statuses and reported a negative correlation between FTD and SE (mean –2.16 ± 2.40 D), with lower SE values associated with higher FTD. Likewise, Li et al 9 conducted a study involving 1084 young adults aged 17–23 years. They quantified FTD and investigated associated factors, including subfoveal choroid thickness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They further examined FTD variations in different refractive statuses and reported a negative correlation between FTD and SE (mean –2.16 ± 2.40 D), with lower SE values associated with higher FTD. Likewise, Li et al 9 conducted a study involving 1084 young adults aged 17–23 years. They quantified FTD and investigated associated factors, including subfoveal choroid thickness.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that for PM patients, the “X” method is more suitable, and the 6.0-mm diameter centered on the macular is more representative. Li et al adopt the method of “X” and found that 3.0 and 6.0 mm were associated with longer AL and thinner subfoveal choroid thickness 9 . While for the optic disc, the different methods are all suitable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations